A rheumatological dilemma: is it possible to modify the course of rheumatoid arthritis? Can we answer the question?. Issue 2 (February 1985) - Pullar, T; Capell, H A
Abstract : The question 'Does the use of second-line therapy confer long-term benefit on outcome measures in rheumatoid arthritis?' remains unanswered. The major obstacle which prevents collection of the necessary data is the lack of a suitable control group. In this report experience with three 'second-line placebo groups' is described, and previous studies in the literature which incorporated a placebo group are reviewed. In the absence of concurrent corticosteroid therapy very few patients remain on placebo second-line medication after one year. Those that do, appear to have milder disease and are not representative of the group as a whole. Data on outcome measures need to be collected over two to five years, but the answer to the question which is posed does not depend upon larger and larger placebo groups which constitute increasing bias. To define the extent of benefit offered by the more powerful therapeutic agents a novel approach in regard to drug assessment will be required.